Cost-effectiveness analysis of typhoid vaccination in Lao PDR - Mick Soukavong; Nantasit Luangasanatip; Phetsavanh Chanthavilay; Yot Teerawattananon; Saudamini Vishwanath Dabak; Wirichada Pan-ngum; Tamalee Roberts; Elizabeth A Ashley; Mayfong Mayxay (BMC, 2023)
Abstract Background Typhoid vaccination has been shown to be an effective intervention to prevent enteric fever and is under consideration for inclusion in the national immunization program in Lao PDR. Methods A cost-utility analysis was performed using an age-structured static decision tree model to estimate the costs and health outcomes of introducing TCV. Vaccination strategies combined with five delivery approaches in different age groups compared to no vaccination were considered from the societal perspective, using the Gavi price of 1.5 USD per dose. The vaccination program was considered to be cost-effective if the incremental cost-effectiveness ratio was less than a threshold of 1 GDP per capita for Lao PDR, equivalent to USD 2,535 in 2020. Results In the model, we estimated 172.2 cases of enteric fever, with 1.3 deaths and a total treatment cost of USD 7,244, based on a birth cohort of 164,662 births without TCV vaccination that was followed over their lifetime. To implement a TCV vaccination program over the lifetime horizon, the estimated cost of the vaccine and administration costs would be between USD 470,934 and USD 919,186. Implementation of the TCV vaccination program would prevent between 14 and 106 cases and 0.1 to 0.8 deaths. None of the vaccination programs appeared to be cost-effective. Conclusions Inclusion of TCV in the national vaccination program in Lao PDR would only be cost-effective if the true typhoid incidence is 25-times higher than our current estimate.